Are Local Tax Rates Strategic Complements or Substitutes? - Raphael Parchet (European Regional Science Association (ERSA), 2012)
The identification of strategic interactions among local governments is typically plagued by endogeneity problems. This paper proposes a quasi-experimental strategy to identify independent personal income tax setting by Swiss municipalities making use of the multi-tier federal system. State (cantonal) borders spatially bound the effects of canton-level fiscal reforms in areas that are otherwise highly integrated. Fiscal reforms at the canton level provide an exogenous source of variation in municipal tax rates, and are thus a valid instrument to identify strategic interactions among municipalities located at a cantonal border. In contrast to most of the existing empirical literature, I find that tax reaction functions have a negative slope and that taxes rates are strategic substitutes rather than strategic complements. This is compatible with a model of local tax setting in which governments primarily target expenditure rather than tax receipts.
Keywords: H24; H71; H77; 330; tax competition; fiscal federalism